2008
DOI: 10.1016/j.juro.2007.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Association of Surgeon Subjective Characterization of Nerve Sparing Quality With Potency Following Laparoscopic Radical Prostatectomy

Abstract: Cavernous nerve preservation during laparoscopic radical prostatectomy is not an all or none phenomenon. A surgeon subjective sense of neurovascular bundle sparing quality may aid in accurately characterizing the return of sexual function following laparoscopic radical prostatectomy. Partial nerve preservation may lead to an incremental improvement in the return of sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
1
25
1
Order By: Relevance
“…Heavier men were shown to have worse cavernous nerve-sparing as subjectively graded intra-operatively, a finding that has been correlated with recovery of erectile function. 23 Furthermore, we found that obese men underwent PLND less frequently, a finding that is not explained by differences in pre-operative tumor characteristics. As LRP/RARP are technically feasible, even in extremes of obesity, obesity should not contraindicate PLND when it is otherwise indicated.…”
Section: Commentmentioning
confidence: 57%
See 1 more Smart Citation
“…Heavier men were shown to have worse cavernous nerve-sparing as subjectively graded intra-operatively, a finding that has been correlated with recovery of erectile function. 23 Furthermore, we found that obese men underwent PLND less frequently, a finding that is not explained by differences in pre-operative tumor characteristics. As LRP/RARP are technically feasible, even in extremes of obesity, obesity should not contraindicate PLND when it is otherwise indicated.…”
Section: Commentmentioning
confidence: 57%
“…Subjective NSS takes into account both nerve-sparing quantity and quality, and is in use by various groups in the United States. 23-25 The relation between BMI and nerve-sparing quality has not previously been assessed to our knowledge, though prior studies have demonstrated mixed results with respect to BMI and nerve-sparing frequency . 13,26,27 In addition, on multivariable analysis, higher BMI category was found to be an independent predictor of longer OT, suggesting added surgical difficulty inherent in operating on the obese patient, even with a minimally-invasive approach.…”
Section: Commentmentioning
confidence: 99%
“…This particular grading scheme for nerve injury has received criticism in recent years for its inability to accurately describe the degree of neurovascular damage and thus yielding imprecise and varying EFR rates in studies (Burnett et al, 2007;Marien et al, 2009;Tal et al, 2009;Moskovic et al, 2011). As EFR can be significantly affected by the degree of nerve damage, it therefore follows that assessing nerve damage using a binary 'all-or-nothing' scheme ignores nuances crucial to patient EF outcomes (Levinson et al, 2008;Rabbani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nerve-sparing quality in each case was subjectively graded by the operative surgeon on a 0 (none) to 4 (excellent) scale/neurovascular bundle, resulting in a nerve-sparing score (NSS) of 0 to 8. 8 Urinary function was initially assessed by the EPIC questionnaire, and then again after RP at 1, 3, 6, 9, 12 months, and after a 1 month PDE5i washout period (13 months postoperatively). Specific EPIC urinary subscales were used for the analyses presented in the current study: urinary domain summary score (USS): urinary irritative/obstructive subscale, also termed urinary irritative subscale (UIR); urinary bother subscale (UBS); urinary incontinence subscale (UIN); and urinary function subscale (UFS), with higher scores representing better health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%